2005
DOI: 10.1021/ja050507f
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-Selective Solubilization of Single-Walled Carbon Nanotubes by Reversible Cyclic Peptides

Abstract: We have utilized reversible cyclic peptides (RCPs)-peptides containing alternating l- and d-amino acids with N- and C-termini derivatized with thiol-containing groups allowing reversible peptide cyclization-to solubilize and noncovalently functionalize carbon single-walled nanotubes (SWNTs) in aqueous solution. Solubilization occurs through wrapping of RCPs around the circumference of a SWNT, followed by the formation of head-to-tail covalent bonds, yielding closed rings on the nanotubes. By controlling the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 26 publications
5
148
0
2
Order By: Relevance
“…in 2002, 71 ultrasonic processing has been used to isolate SWNTs in an extensive library of dispersing agents including surfactants, 119,130 polymers, 120 single-stranded DNA, 19,132,133 peptides, 134 and cagelike molecules such as Sarkosyl. 135 Figure 3-1 contrasts the appearance of an aqueous suspension containing mostly bundles and an aqueous sample enriched in isolated SWNTs.…”
Section: Motivationmentioning
confidence: 99%
“…in 2002, 71 ultrasonic processing has been used to isolate SWNTs in an extensive library of dispersing agents including surfactants, 119,130 polymers, 120 single-stranded DNA, 19,132,133 peptides, 134 and cagelike molecules such as Sarkosyl. 135 Figure 3-1 contrasts the appearance of an aqueous suspension containing mostly bundles and an aqueous sample enriched in isolated SWNTs.…”
Section: Motivationmentioning
confidence: 99%
“…For example, it has been shown that open single-walled carbon nanotubes can accommodate small proteins such as cytochrome c inside their internal cavities, leading to the stable immobilization of the proteins in bioactive conformations [114]. Ortiz-Acevedo et al used a novel class of cyclic peptides containing alternating L-and Damino acids (AAs), called reversible cyclic peptides (RCPs), for the diameter-selective solubilization of HiPco single-walled carbon nanotubes [115] . In L-/D-peptides, all side chains reside on one face of the backbone, encouraging a ringlike conformation with the side chains on the ring exterior.…”
Section: Cnts/protein Conjugatesmentioning
confidence: 99%
“…As a result, alternative approaches using the non-covalent adsorption of surfactants (O'Connell, Bachilo et al 2002), polymers (Dalton, Blau et al 2001) and biomolecules Numata, Asai et al 2005) to solubilize the SWCNTs have been proposed and tested. To that end, much research attention has been focused on the design and utilization of polypeptide/CNT complexes because of their functionality in biological systems (Dieckmann, Dalton et al 2003;Zorbas, Ortiz-Acevedo et al 2004;Ortiz-Acevedo, Xie et al 2005;Pender, Sowards et al 2005;Karajanagi, Yang et al 2006;Su, Leung et al 2006) recently. We investigated the binding nature of three peptides (inactive NB1 and active B1 and B3) to single-walled carbon nanotubes (SWCNTs) using a density functional tight-binding (DFTB) method with an empirical vdW force correction (Fan, Zeng et al 2009).…”
Section: Peptidesmentioning
confidence: 99%